Iterative Learning Control of Discrete Systems with Actuator Backlash using a Weighted Sum of Previous Trial Control Signals - Pakshin, Pavel; Emelianova, Julia; Rogers, Eric; Gałkowski, Krzysztof
This paper considers iterative learning control design for discrete dynamics in the presence of backlash in the actuators. A new control design for this problem is developed based on the stability theory for nonlinear repetitive processes. An example of this design`s effectiveness is where the dynamics model was obtained using data collected from frequency response tests on a physical system.
Keywords: iterative learning control; nonlinear dynamics; repetitive processes